Response to the Letter to the Editor Regarding "Survey among Medical Students during COVID-19 Lockdown: The Online Class Dilemma" - Andrew Thomas; Mohan. T Shenoy; Kottacherry T. Shenoy (University Library System, University of Pittsburgh, 2020)
We thank the editor for allowing us to respond to the comments by Akshara et al. The authors concur with us on unpreparedness and goes on to highlight how female doctors are over-worked during the pandemic. In this response, we also discuss why providing free data will not bring about significant change in students' perception of online classes. We then advise how students can learn basic examination skills during the pandemic. Finally, we express our views on government and universities and finish with a recommendation that would help future doctors in times like the COVID-19 pandemic.